Reason as Embodied, Metaphorical, and Imaginative - Godwins, Jude (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
Studies in cognitive science provide three crucial empirical findings about the nature of the human mind. First is the inherently embodied nature of the mind. Second is predominantly unconscious nature of the human thought. Third is the principally metaphorical character of our abstract concepts. In a previous study, it was our intention to suggest the manner in which, when all is said and done, our power of abstract reason, under the framework proposed by proponents of imaginative reason, and reinforced by a host of thinkers sympathetic to their views, could well be identified with the human conceptualizing capacity. This has been found to involve three factors.The first factor is the power to create symbolic constructs corresponding to preconceptual structures in our common place experience. These preconceptual structures are the basic-level (walking, running) and image-schematic concepts (spatial space). The second factor is the power of metaphorical mapping, framing structures in the physical sphere onto constructs in the abstract realms–all within the framework of the existing structural correspondences between the abstract and the physical horizons. This constraint belongs to the system. Our image schematic and metaphorical structures prohibit some movements (inferences), making them simply impossible. Here in lies our capacity for abstraction. Finally, the third factor is the power to employ image schemata as structuring schemes in the creation of general categories and complex concepts. Thus, we can form structures of complex events and taxonomies that have subordinate (e.g., types of walking and running) and superordinate (e.g., movement) categories.